UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH PESERTA DIDIK MELALUI PEMBELAJARAN SAINTIFIK DI SMA NEGERI 25 PULAU MAKIAN KECAMATAN MAKIAN BARAT - Asri Tamalene; Karmila Ade; Eko Purnomo (EDUKASI, 2021)
This study aims to (1) determine the implementation of scientific learning at SMA Negeri 25 Pulau Makian, Kec. Makian Barat, and (2) Improving students' scientific thinking skills through scientific learning. This study is a classroom action research (Class Room Action Research). The design of study used Kemmis and McTaggart model which included four steps (steps): (1) planning; (2) actions; (3) observation; and (4) reflection. Data collection techniques were carried out by (1) Test, test used to determine students' scientific thinking skills, (2) observation is conducted to observe the learning process using a scientific approach model. The observation  focus on the implementation of learning by teachers starting from initial activities, core activities, and final activities, as well as student activities in learning, and (3) documentation used to take pictures/photos of the implementation of learning by teachers and student activities in learning. Students' scientific thinking ability was analyzed qualitatively with a scale of five categories, the implementation of learning by teachers was analyzed qualitatively with a scale of five categories, and students' learning activities were analyzed qualitatively with a scale of four categories. The results showed that (1) the average percentage of students' scientific thinking skills in cycle one obtained a value of 24% with very poor criteria and increased in cycle two by 75% with good criteria, and (2) the average percentage of learning implementation by the teacher in the first cycle obtained a score of 87% with very good criteria and increased again in the second cycle by 100% with the same criteria. Meanwhile, for student activity, the average percentage of cycle one is 71% with high criteria and has increased in cycle two by 82% with very high criteria.